2015
DOI: 10.1007/s00247-015-3432-7
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric appendiceal ultrasound: accuracy, determinacy and clinical outcomes

Abstract: US should be the initial imaging study of choice for pediatric appendicitis. When a definitive interpretation was given, the accuracy was 96%, was independent of patient and system factors and resulted in reduced follow-up CTs and negative laparotomies. Accuracy can be increased by requiring the presence of periappendiceal inflammatory changes prior to interpreting a mildly distended appendix as positive for acute appendicitis. The indeterminate study rate can be reduced by not requiring visualization of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
47
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 35 publications
6
47
1
Order By: Relevance
“…This is very much the case in acute appendicitis where history, physical exam, and laboratory and imaging data all contribute to the diagnosis and possible management strategies include further imaging, nonintervention, antibiotic therapy, immediate surgery and delayed surgery. Data from the current study by Binkovitz et al [1] and from our prior study [2] demonstrate the value of information that is available in equivocal ultrasound results. In both studies, the likelihood of appendicitis in a sonographically equivocal case (12.9-24.3% in Binkovitz et al [1], 25.8-39.3% in Larson et al [2]) is distinctly different from the likelihood in a clearly positive (86.5% in Binkovitz et al [1], 92.6% in Larson et al [2]) or negative case (2% in Binkovitz et al [1], 2.6% in Larson et al [2]).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…This is very much the case in acute appendicitis where history, physical exam, and laboratory and imaging data all contribute to the diagnosis and possible management strategies include further imaging, nonintervention, antibiotic therapy, immediate surgery and delayed surgery. Data from the current study by Binkovitz et al [1] and from our prior study [2] demonstrate the value of information that is available in equivocal ultrasound results. In both studies, the likelihood of appendicitis in a sonographically equivocal case (12.9-24.3% in Binkovitz et al [1], 25.8-39.3% in Larson et al [2]) is distinctly different from the likelihood in a clearly positive (86.5% in Binkovitz et al [1], 92.6% in Larson et al [2]) or negative case (2% in Binkovitz et al [1], 2.6% in Larson et al [2]).…”
supporting
confidence: 64%
“…We were pleased to see the article "Pediatric Appendiceal Ultrasound: Accuracy, Determinacy and Clinical Outcomes" by Dr. Binkovitz and colleagues [1] in which the authors describe a six-category interpretive scheme for ultrasound of the appendix. The scheme that they describe is very similar to a five-category scheme that we recently published [2].…”
mentioning
confidence: 99%
“…Nielsen et al [5] have found that the introduction of a US reporting scheme that did not include indeterminate categories decreased both the rate of follow-up CT studies and negative laparotomies while increasing US sensitivity and accuracy [5]. The results from our study identified ways to increase determinacy and accuracy [2] and we have begun to implement these changes while monitoring for negative outcomes.…”
mentioning
confidence: 62%
“…Trout and Larson [1] concerning our article in this issue of Pediatric Radiology and the opportunity to further this discussion with a few additional thoughts. There are striking similarities between our two studies with respect to design and results but there are substantial differences in the conclusions drawn [2,3].…”
mentioning
confidence: 63%
See 1 more Smart Citation